HYPERURICEMIA INFLUENCE ON THE STATE OF PLATELET HEMOSTASIS IN PATIENTS WITH STAGE II HYPERTENSION - M.S. Valigura (Bogomolets National Medical University, 2018)
Summary. The effect of uric acid on platelet hemostasis in patients with hypertension (HT) was studied. 80 patients with the HT I-II stage and 1-3 degrees of increased blood pressure was examined. Hyperuricemia was diagnosed with a uric acid level of>420 мmol/L. In order to study platelet hemostasis, an estimate of spontaneous aggregation of platelets and induced aggregation with adenosine diphosphate (ADP), arachidonic acid (AA), collagen, and adrenaline before and after cuff tests was performed. An assessment of endothelial dysfunction during cuff tests was also performed. Hyperaggregation was detected in all patients on HT. It was more significant in hypertensive patients with hyperuricemia and it was dependent on the level of uric acid in plasma.